Narative Review: Strategi Pengembangan Sumberdaya Manusia di Rumah Sakit untuk meningkatkan Profesionalisme dan Layanan - Lia Qelina; Rinawati Rinawati (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
The health sector, especially hospitals, relies heavily on the competence and professionalism of human resources to provide high quality services. Strategic development of human resources (HR) is the key to achieving organizational goals and improving service quality. This narrative literature review discusses strategic HR development in the hospital environment with a focus on three main pillars: training programs, leadership development, and performance evaluation. Findings show that training helps health workers adapt to advances in technology and medical innovation; leadership development drives accountability and collaboration which is critical in complex environments; and performance evaluation supports continuous improvement by identifying development needs and aligning individual contributions with organizational goals. The integration of these three strategies increases professionalism, operational efficiency and service quality in hospitals. Future research is recommended to examine how this HR development strategy can be adapted in various health care contexts to ensure its sustainability and effectiveness.